Quaternary climates, environments, and magnetism - Maher, Barbara A. 1960-; Thompson, Roy 1948 August 23- (Cambridge University Press, 1999)
The Quaternary has been a period of major climatic and environmental oscillations, and our knowledge of these past variations is important for our understanding of the possible impact of human activity on the present-day environment. First published in 1999, Quaternary Climates, Environments and Magnetism presents an account of the rich variety of uses of magnetic measurements in the environmental geosciences. Ten chapters by leading world authorities describe the highlights of environmental magnetic work during the last decade and identify directions for future research. Emphasis is placed on a multidisciplinary approach to achieve a more thorough understanding of the environmental processes involved. This volume will be of interest to research scientists from a wide range of disciplines working on Quaternary environments, including earth and environmental sciences, physical geology, geography and palaeoclimatology. It will also be valuable as a supplementary text for graduates and advanced undergraduates.